PERAN GURU MENANAMKAN BUDAYA SEKOLAH UNTUK PENDIDIKAN KARAKTER: STUDI KASUS SALAH SATU SEKOLAH SWASTA DI KOTA BANJARMASIN - Lisa Hartini; Ahmad Suriansyah; Ratna Purwanti (Komunitas Manajemen Kompetitif, 2025)
School culture is the main foundation in shaping students' character. This article discusses the strategic role of teachers in instilling school culture for character education enhancement, based on a case study in a private school in Banjarmasin. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with teachers and school principals, and documentation of school activities. The results show that teachers act as role models, facilitators, and main drivers in building character values through habituation, integration of values in the curriculum, and extracurricular coaching. However, several obstacles were found such as limited time, diverse student characters, and environmental support. This study recommends strengthening teacher training and collaboration between schools and parents to create an effective school culture for building students' character. Keywords: Teacher’s Role, School Culture, Character Education, Case Study, Banjarmasin